Comparative study between methods of pre-operative measurement of intramedullary nail length in fracture shaft of femur - Mat Rodi, Mohd Saiful Adzuwan (2015)

(untitled)
Introduction Fractures shaft of the femur are among the most common fractures encountered in orthopaedic practice. Locked femoral intramedullary nailing is accepted as the standard treatment of choice for most femoral shaft fractures. As most of operation room inventory in our setup does not have a complete range of the intramedullary nails, most surgeons estimate the size and length of the intramedullary nail preoperatively by various methods and keep a size bigger and smaller the assessed length for the planned surgery. Objective The main objective was to study the accuracy and validity of pre-operative clinical measurement of intramedullary nail length in fracture shaft of femur. We also studied the inter-observer reliability of each method tested. Methodology This research was a prospective randomized study that involved analysis of data taken clinically as well from plain radiograph. This study was done as a clinical assessment. One hundred and thirty patients were enrolled. Measurement of femoral shaft was performed by using three different methods, which were tested by three investigators from different level of medical background. Method 1 was measurement taken from the tip of greater trochanter to the lateral knee joint line of the opposite limb minus 2 centimeters (standard AO), Method 2 was measurement taken from the tip of the greater trochanter to the upper pole of patella on the opposite limb (alternative AO) and Method 3 was measurement taken from the tip of the olecranon process to the tip of the little finger on any side (the “tip-to-tip” method). Results Analysis showed that there were significant differences in inter-observer variability in the measurement taken using Method 1 (p = 0.0001) and Method 2 (p = 0.0001) but not in Method 3 (p = 0.763). All methods were well correlated with radiology measurements. The average length of measurement for Method 3 were 1.7 cm longer in female patients and 2.5 cm longer in male patients than average length of measurement by radiograph. Conclusions Method 3 is valid and can be applied in clinical practice with accuracy by subtracting 1.7 cm from the measurement in a female patient and 2.5 cm from the measurement in a male patient. It also has significant inter-observer reliability. It is simple to perform, radiation-free and can be applied in a patient with bilateral femur fractures.